Project almanac [videorecording (DVD)] - Weston, Jonny; Black-D'elia, Sofia; Lerner, Sam, 1993- (Paramount Home Entertainment, 2015)
A brilliant high school student and his friends uncover blueprints for a mysterious device with limitless potential, inadvertently putting lives in danger.